Management and supervisory practices for environmental professionals. Volume 2, Advanced competencies - Koren, Herman; Anderson, Alma Mary (Boca Raton, FL : CRC Press, 2021)
Based on the lifelong experiences of two authors as supervisors and teachers, the Fourth Edition of this bestseller provides up-to-date information for newly promoted or management-aspiring professionals and engineers in the fields of environmental health, occupational health and safety, water and wastewater treatment, public health, and many others. This second volume explains the advanced principles that supervisors need to understand the art of communications, resolving communications problems, and the supervisor/manager's role in teaching, counseling, and managing employee performance and employee health and safety. In addition to those already practicing professionals in their fields, this book is an excellent resource for students interested in learning management skills prior to entering the workforce. Features of the Fourth Edition Helps to understand and utilize organizational structure to facilitate problem solving Offers a practical set of methods, tools, and techniques, all illustrated and easy to understand, for achieving leadership qualities Provides concise but essential discussion material for each topic, using the practical art of communications Includes thorough updates and many new case problems with answers provided Introduces self-testing questions for different situations and practical exercises utilizing an individual's own work experience for answers
OCLC-licensed vendor bibliographic record.
Keywords: Supervision of employees; Personnel management; LAW / Environmental; BUSINESS & ECONOMICS / Human Resources & Personnel Management